The Retinoblastoma Tumor Suppressor Pathway Modulates the Invasiveness of ErbB2 Positive Breast Cancer - Witkiewicz, Agnieszka K. (2013)
The processes that control the progression of ductal carcinoma in situ (DCIS) to invasive breast cancer remain poorly understood. Epidermal growth factor receptor 2 (ErbB2) over expression is common in DCIS, as is disruption of the retinoblastoma tumor suppressor (RB) pathway. Here we examined the cooperative impact of ErbB2 and RB deregulation on facets of disease progression. Our studies demonstrate that RB deficiency altered the expression of key molecules needed for proper cellular organization and epithelial cell-cell adhesion as part of a program related to the epithelial to mesenchymal transition (EMT). An increase in the invasive potential of ErbB2 over expressing cells was observed upon RB depletion. Furthermore, stable knockdown of RB resulted in invasive lesions in orthotopic xenograft assays, compared to DCIS-like lesions developing from RB-proficient cells. Conversely, the invasive phenotype observed in ErbB2-positive cancer models was inhibited through CDK4/6 inhibition in an RB-dependent manner. Lastly, in a cohort of DCIS cases, we show that while elevated levels of ErbB2 are associated with increased risk of a subsequent DCIS recurrence, it is not associated with progression to invasive disease. In contrast, RB loss in ErbB2 positive DCIS cases was associated with increased risk for invasive breast cancer. Taken together, these data demonstrate a key role for the RB-pathway in invasion associated with breast tumor progression, and shed light on the key molecular events that promote the progression of DCIS to invasive disease.